PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI FABEL BERBANTUAN KINEMASTER ERHADAP KETERAMPILAN MENYIMAK BAHASA INDONESIA PADA KELAS IV SEKOLAH DASAR - Rahmadani, Dzikra; Muhammadi; Adrias; Muhammad Habibi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Listening skills are a crucial aspect of language proficiency to be cultivated in elementary school students. However, observations in several elementary schools indicate that Indonesian language instruction remains dominated by lecture methods and textbook usage, preventing students' listening skills from developing optimally. This study aimed to develop valid, practical, and effective animated fable video learning media using the KineMaster application to enhance the listening skills of fourth-grade elementary school students. The study employed the Research and Development (R&D) method using the ADDIE development model, comprising the analysis, design, development, implementation, and evaluation stages. The research subjects included expert validators, teachers, and fourth-grade elementary school students. Data were collected through observations, interviews, questionnaires, and tests, and subsequently analyzed using descriptive quantitative methods. The results demonstrated that the developed media achieved an average validity score of 94.5% (categorized as "very valid"); practicality scores of 96% in the trial school and 94% dan 97.68% in the implementation schools (categorized as "very practical"); and effectiveness evidenced by an increase in the average score from 73.8 (pretest) to 97.6 (posttest), with an N-Gain score of 90.8% (categorized as "high"). Consequently, the animated fable video learning media created with KineMaster is deemed valid, practical, and effective, making it a suitable alternative for Indonesian language instruction to improve the listening skills of fourth-grade elementary school students.